Technology Enhanced PBL in HCI Education: A Case Study - Zaphiris, Panayiotis; Ioannou, Andri; Vasiliou, Christina (My University, 2013)
Problem Based Learning (PBL) is an instructional method in which the base for learning is a real-world problem. A typical PBL setting is comprised of students working together on an authentic problem, using simple tools such as whiteboards and stationery. Online tools and multimedia technologies have also been used to support PBL activities. There is however no empirical work on the blended use of both physical and digital tools. This paper presents a case study in which we employed PBL pedagogy for the teaching of a postgraduate course in Human Computer Interaction (HCI). The activities were situated in a multimodal information space, rich in digital and physical elements including personal computers, projectors with downwards projection, tablets, iPods, digital pen readers, stationery and a Facebook group for each team. We administrated questionnaires assessing students’ motivational beliefs and overall satisfaction with the learning experience. Our results show that students’ overall satisfaction was highly rated, while the information space contributed to students’ engagement and collaboration.
Keywords: Problem based learning; HCI education; Multi-modal interfaces